Strengthening Madrasah Organizational Culture: Integration of Religious Values in Character Education in Madrasah - Kholifah, Khusnul; Fanani, Ahmad Aziz; Hidayah, Fathi; Bannaga Taha Elzubair Hussen; Baharun, Hasan (STAI Terpadu Yogyakarta, 2024)
This study aims to investigate (1) curriculum integration, (2) values that are the basis of the learning process, (3) activities/programs developed, and (4) the involvement of parents and the community in character education in madrasas. This study uses a qualitative research method with a case study approach, with data collected from school principals, teachers, students, madrasah staff, and official madrasah documents. Data collection techniques include in-depth interviews, participatory observations, and document analysis. The data that has been collected is analyzed using thematic analysis techniques. The results of the study show that (1) the integration of the curriculum in Madrasah Ibtida'iyah Banyuwangi has succeeded in combining religious values in each subject, (2) the values that are the basis of the learning process, such as honesty and responsibility, are applied in various subjects, (3) activities/programs such as Tahfidz Qur'an and other extracurricular activities support the development of students' character, and (4) the involvement of parents and the community significantly supports strengthening student character education. So, to ensure the validity of the findings, data triangulation techniques are used to compare information from different sources and data collection methods. These results emphasize the importance of a holistic approach to character education based on religious values involving various education components.